IMPROVING THE APPLICATION OF INFORMATION TECHNOLOGY IN EDUCATION - Abdullaev Sharof Abdugafforovich (Galaxy International Interdisciplinary Research Journal, 2021)
The article is devoted to improving the application of information technology in education. Scientifically based proposals and recommendations for the effective organization of these processes have also been developed.